THE PRACTICE OF CONSOLIDATING THE SPIRITUAL AND IDEOLOGICAL FACTOR OF THE NATIONAL SOCIETY IN THE NEW LEVEL OF RESEARCH (Scientific journal of the Fergana State University, 2024)
In this article, at the new stage of the development of our country, the philosophical aspects of the practice of strengthening the spiritual factors and ideological principles of the development of the civil society in the social life and its reflection in the social consciousness of the citizens are analyzed and specific scientific conclusions are given.